Oxford India Srinivas - Srinivas, Mysore Narasimhachar (New Delhi : Oxford University Press, 2009)
Articles chiefly on various aspects of social change in India.
Includes bibliographical references (p. [714]-725) and index.
Keywords: Social change -- India